Aplikasi Mikrotik Dasar Sebagai Pembatasan Bandwidth pada Warung Internet Teranet One di Prabumulih - Rahmat Novrianda Dasmen; Kharisma Pangestu; Kevin Saputra (J-ICON : Jurnal Komputer dan Informatika, 2022)
With the development of information technology, the need for the use of the internet is becoming increasingly important in helping daily life. Computer network support equipment is still very much needed. Currently the internet is not only needed to do office work but also to communicate, play games and do school work. Mikrotik has the most important task in building a computer network system. Mikrotik is a computer network hardware that can transmit data to the network. Mikrotik also acts as a liaison between many networks to transfer data from one network to another. Mikrotik is priced at a fairly high price and is still difficult to reach by the general public, so an operating system is formed, namely Mikrotik Router OS. Mikrotik Router OS is a solution for those who need a reliable router only with a personal computer (standalone) with the Mikrotik operating system. The internet cafe (warnet) of Teranet One is experiencing a bandwidth leak problem where users can access the internet without any bandwidth restrictions. Therefore, it takes a bandwidth limitation system using Mikrotik. With this bandwidth limitation system, bandwidth leaks can be overcome and the upload and download speeds of each user can be regulated.